Family Involvement in Managing Work–Life Balance for Elderly Safety: A Case Study of Harapan Kita Nursing Home, Ogan Ilir, Indonesia - Herlina, Herlina (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
Abstract The transfer of the care, treatment, and upbringing of elderly parents to nursing homes has become a trendy phenomenon today. Most of the reasons for this care are due to the busy work and routine activities of the family, especially children, so that the intensity of attention and affection for the parents who are entrusted. However, this reason is not justified in Islamic law as long as children and families are still able to take care of elderly parents. Many cases of neglect of the elderly in care or being cared for by others and maintenance do not meet physical and mental health standards. There needs to be intensive supervision of elderly people who are entrusted to nursing homes, especially physical, psychological, and spiritual security. This article examines how to control quality, efficient, and effective time so that the intensity and frequency of family visits, especially children to nursing homes, can be carried out properly. The analysis and measurement of research data uses a qualitative approach with a descriptive level of explanation and is field research. Cases that occur in the field reflect the need for quality, efficient, effective time management of routine activities and family work so that visiting activities can consistently be carried out every week. This is because attention and affection from children and family play an important role in the lives of the elderly. Time management must be arranged in such a way that children and families have a frequent schedule to visit parents who are entrusted to the nursing home. The remaining time must be utilized by children and parents so that the blessing of life is maintained properly and nobly. [Pengalihan pemeliharaan, perawatan dan pengasuhan orang tua lanjut usia ke panti jompo telah menjadi fenomena tren pada saat ini. Sebagian besar alasan penitipan ini dikarenakan oleh kesibukan bekerja dan aktivitas rutin keluarga, khususnya anak sehingga berkurangnya intensitas perhatian dan kasih sayang terhadap orang tua yang dititipkan. Namun, alasan tersebut kurang dibenarkan dalam syariat Islam selama anak dan keluarga masih mampu mengurusi orang tua lansia. Banyak kasus penelantaran lansia di penitipan atau dirawat oleh orang lain dan pemeliharaan kurang memenuhi standar kesehatan fisik serta mental. Perlu adanya pengawasan yang intensif terhadap orang tua yang dititipkan di panti jompo, terutama keamanan fisik, psikis, dan spiritual. Artikel ini meneliti tentang cara mengendalikan waktu yang berkualitas, efisien dan efektif agar intensitas serta frekuensi kunjungan keluarga, khususnya anak ke panti wredha dapat terlaksana dengan sebaik-baiknya. Analisis dan pengukuran data penelitian menggunakan pendekatan Kualitatif dengan tingkat eksplanasi Deskriptif dan bersifat Field Research. Kasus yang terjadi di lapangan mencerminkan perlu adanya manajemen waktu yang berkualitas, efisien, efektif terhadap aktivitas rutinitas dan kerja keluarga agar kegiatan berkunjung secara konsisten dapat dilakukan setiap minggu. Hal ini mengingat perhatian dan kasih sayang dari anak dan keluarga memiliki peran penting dalam kehidupan lansia. Manajemen waktu harus diatur sedemikian rupa sehingga anak dan keluarga memiliki jadwal yang sering untuk mengunjungi orang tua yang dititipkan di panti jompo. Waktu yang tersisa harus dimanfaatkan oleh anak dan orang tua agar keberkahan hidup tetap terjaga dengan baik dan mulia.]